Nanoprobe synchrotron X-ray fluorescence microscopy reveals selenium-rich spherical structure in mouse retinal pigment epithelium - Marta Ugarte; Kalotina Geraki; Elizabeth Bentley; Roger Cox (Scientific Reports)
Abstract High-resolution nano-focus X-ray fluorescence microscopy using hard X-rays at the European Synchrotron Radiation Facility (ESRF) IDB16 beamline detected endogenous barium, bromine, calcium, chlorine, copper, iron, manganese, potassium, phosphorus, rubidium, sulphur, selenium, strontium and zinc, at tissue, cellular and subcellular level in the outer retinal complex of light adapted, 3-week-old, male C57BL6 mice. Fresh snap-frozen (20 μm) cryosections dried at room temperature were scanned at 1 μm, 300 nm and 50 nm spatial resolution by incident X-ray photons from the synchrotron beam. Analysis of 2D maps and 3D surface plots by PyMCA and ImageJ revealed elevated zinc concentrations in the choriocapillaris (CC) (mean 45, range 28–77 ppm), retinal pigment epithelium (RPE) layer (mean 47, range 20–76 ppm), photoreceptor inner segments (RIS) ellipsoid zone, outer limiting membrane (OLM) (mean 32, range < 1–44 ppm) and outer nuclear layer (ONL) in between photoreceptor cell bodies. Mūller cells processes in ONL and their interdigitations in RIS ellipsoid zone seem to contain zinc in the cell membrane. Iron was found at elevated amounts in RIS myoid zone (mean 38, range 14–68 ppm), RPE layer (52, range 24–143 ppm), and choroid (60, range 36–172 ppm). Copper was also detected in the CC (4.3, range 1.9–9.7 ppm), RPE layer (4.5, range 1.6–20.8 ppm), and RIS myoid zone (4.9, range 1.25–10.2 ppm). Calcium was found with granular/punctate distribution in OLM (159, range 49–962 ppm), RIS myoid zone (245, range 36-1370 ppm), RPE layer (1134, range 257–2503 ppm), and CC (1101, range 323–2090 ppm). The metalloid selenium was present in the CC (1.8, range < 1-4.7 ppm] and across the RPE (basal, central, apical) (2.4, range < 1-8.5 ppm). High resolution maps of the interface photoreceptor outer segments (ROS) and the RPE apical side revealed selenium-rich spherical structures (appr. 1 μm diameter) (mean 5.6, range 2.2–8.1 ppm), associated with calcium (mean 1057, range 619–1755 ppm), phosphorus (9924, range 6118–15058 ppm), and manganese (0.7, < 1–24 ppm), surrounded by a zinc-containing layer. This study presents the first nanoprobe X-ray fluorescence microscopy image analysis of adult mouse light adapted outer retinal complex from the whole tissue to subcellular structures. The high spatial resolution (location) and high sensitivity (metal quantity) findings, together with the information on biometals available in the literature, allowed us to propose a schematic model of possible selenium biological processes and their role in physiological activities in the outer retinal complex. We hypothesise there is a dedicated selenium-rich spherical structure with the ability to cross RPE cell membranes (i.e. the outer blood retinal barrier) and with potential roles in certain biological function(s) (e.g. ROS phagocytosis by RPE cell microvilli, trans-RPE transport).